2008
DOI: 10.1007/s00296-008-0561-4
|View full text |Cite
|
Sign up to set email alerts
|

Chondroprotective effects of glucosamine involving the p38 MAPK and Akt signaling pathways

Abstract: The purpose of the present study was to elucidate the possible signal transduction pathway involved in the underlying mechanism of glucosamine (GLN)'s influence on the gene expression of matrix metalloproteinases (MMPs) in chondrocytes stimulated with IL-1beta. Using chondrosarcoma cells stimulated with IL-1beta, the effects of GLN on the mRNA and protein levels of MMP-3, the activation of JNK, ERK, p38, NF-kappaB, and AP-1, the nuclear translocation of NF-kappaB/Rel family members, and PI3-kinase/Akt activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
0
16
1
1
Order By: Relevance
“…Prior studies have identified the three major MAPKs (ERK1/2, JNK, and p38) (36,37) and PI3K (37) in transmitting IL-1␤-dependent signaling. In light of these findings (36,37), we evaluated the potential contributions of these signaling pathways to shear-induced MMP-9 synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have identified the three major MAPKs (ERK1/2, JNK, and p38) (36,37) and PI3K (37) in transmitting IL-1␤-dependent signaling. In light of these findings (36,37), we evaluated the potential contributions of these signaling pathways to shear-induced MMP-9 synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these findings (36,37), we evaluated the potential contributions of these signaling pathways to shear-induced MMP-9 synthesis. Shear stress rapidly up-regulates the activities of PI3K/Akt, ERK1/2, and JNK/ c-Jun (but not p38) pathways in human T/C-28a2 chondrocytes via an IL-1␤-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vitro studies on the effect of glucosamine on cartilage formation/degradation were provided (Byron et al, 2008;Chan et al, 2005;Derfoul et al, 2007;Dodge and Jimenez, 2003;Largo et al, 2003;Lin et al, 2008;Lippiello, 2007;Lu et al, 2008;Sandy et al, 1999;Shikhman et al, 2001;Toegel et al, 2008;Uitterlinden et al, 2008;Varghese et al, 2007;Wei and Haut, 2009). The applicant was invited to provide a rationale on why any effects of glucosamine in vitro could predict effects in vivo in humans, taking into consideration the experimental conditions for these studies, e.g.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Regarding other proposed mechanisms, the evidence provided included references on in vitro effects of glucosamine on cartilage tissue explants and chondrocytes in culture, including effects of glucosamine on pro-inflammatory cytokines (Chan et al, 2005;Derfoul et al, 2007;Largo et al, 2003;Lin et al, 2008;Lu et al, 2008;Sandy et al, 1999;Shikhman et al, 2001;Toegel et al, 2008), and degradative enzymes (Derfoul et al, 2007;Dodge and Jimenez, 2003;Lin et al, 2008;Lu et al, 2008;Varghese et al, 2007). The Panel notes that the concentrations of glucosamine used in almost all of these studies considerably exceeded those that are achieved in blood and synovial fluid in humans with a daily intake of 1500 mg glucosamine.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Although results of such studies are often difficult to extrapolate to beneficial effects in humans, it appears that, indeed, GlcN does positively influence the biology of damaged issues. These studies ascribe anti-inflammatory properties to GlcN through inhibition of various pro-inflammatory mediators such as nitric oxide, cyclooxygenase-2 (COX-2), matrix metalloproteinases (MMP) but mainly in the context of OA (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). In addition to these mainly site specific studied, Hua et al (28), have reported the inhibitory effect of GlcN on the emergence of adjuvant arthritis (AA) in the rat (29).…”
Section: Evidence For and Against The Beneficial Effects Of Glucosaminementioning
confidence: 99%